Embodied artificial intelligence in ophthalmology - Yao Qiu; Xiaolan Chen; Xinyuan Wu; Yunqian Li; Pusheng Xu; Kai Jin; Xianwen Shang; Peranut Chotcomwongse; Mingguang He; Danli Shi (npj Digital Medicine)
Abstract Embodied artificial intelligence (EAI) integrates perception, memory, reasoning and action through physical interaction, enabling multimodal dynamic learning and real-time feedback. In ophthalmology, EAI supports data-driven decision-making, improving the precision and personalization of diagnosis, surgery, and treatment. It also holds transformative potential in medical education and scientific research by simulating clinical scenarios and accelerating discovery. This perspective highlights EAI’s unique potential while addressing current challenges in data, interpretation, and ethics, and outlines future directions for its clinical integration.